"Trench Town Rock": Reggae Music, Landscape Inscription, and the Making of Place in Kingston, Jamaica. (31st December 2012) - Rhiney, Kevon; Cruse, Romain
Abstract : This paper examines place inscriptions in Trench Town, Jamaica, and explores the ways these are used to reinforce, shape, or challenge dominant images of this inner-city community. On one hand, Trench Town is like many of its neighbouring communities, characterised by high levels of poverty, unemployment, political and gang violence, derelict buildings, and overcrowded homes. On the other hand, Trench Town is iconic and unique as it is recognised worldwide for being the birth place of reggae music and home to a number of well-known reggae artists including reggae superstar Bob Marley. Today, Trench Town's landscape is filled with inscriptions reminiscent of its rich cultural past. Linked to this is a conscious effort by its residents to identify themselves with reggae music and to recapture and sustain the positive legacies that have made the community popular. This is manifested in the numerous murals, statues, and graffiti seen throughout the community evoking past images of reggae music icons such as Marley and Tosh alongside renowned black leaders such as Marcus Garvey. These inscriptions are conceived as texts and are seen as part of a broader discourse on issues relating to urban spatial identity, commoditisation, exclusion, struggle, resistance, and change.